Timing matters? The effects of two different timing of high protein diets on body composition, muscular performance, and biochemical markers in resistance-trained males - Lak, Mohammadyasin; Bagheri, Reza; Ghobadi, Hamid; Campbell, Bill; Wong, Alexei; Shahrbaf, Amin; Shariatzadeh, Mohammad; Dutheil, Fred (Frontiers in Nutrition, 2024)
Background: It is unclear whether resistance training in combination with different timing of protein intake might have differential effects on muscle hypertrophy, strength, and performance. Therefore, we compared the effects of 8 weeks of resistance training combined with two different high-protein diet strategies (immediately pre-and after, or three hours pre and after exercise) in resistance-trained males.Methods: Forty resistance-trained males (24 ± 4 yr) performed 8 weeks of resistance training combined with 2 g . kg -1. d -1 protein. Body composition, muscular performance, and biochemical markers were assessed pre and post-intervention.Results: Nine participants (four from 3hr group and five from the immediate group) withdrew from the study. Therefore, 31 participants completed the study. All measures of skeletal muscle mass, Australian pull-up, and muscle strength, significantly increased post-intervention in both groups (p<0.05). The biochemical marker urea also significantly increased from pre to post in both groups (p<0.05). There were no significant between-group differences (p>0.05).High-protein diet enhances muscular performance and skeletal muscle mass in resistance-trained males, irrespective of intake time. Consequently, the total daily protein intake appears to be the primary factor in facilitating muscle growth induced by exercise.